ANALISIS PENERAPAN AKUNTANSI PIUTANG PADA KPRI BAHAGIA DEPAG KABUPATEN JOMBANG - Ahmadun Ludfi; Putri Laili Nur Malikha; Dwi Ari Pertiwi (ABIDUMASY, 2022)
Cooperative is a business activity carried out by a group of people to achieve common interests and achieve the welfare of its members. The accounting system is used in cooperatives to make managing the company easier. Koperasi Bahagia Depag Cooperative of the Ministry of Religion is a savings and loan cooperative that aims to achieve the welfare of its members. The main activity of this cooperative is savings and loans in the form of short-term and long-term, so that in its implementation it is necessary to have a receivables accounting system so that problems do not arise in its implementation. In this case, of course, proper accounts receivable accounting is needed so that the settlement of receivables can be carried out at a member meeting. The purpose of the study was to find out how the accounts receivable accounting system was applied to cooperatives, and to determine the accounting system used in the loan or receivable cycle at Happy Cooperative of the Ministry of Religion.